An Adaptive Virtual Reality-Based Serious Game for Therapeutic Rehabilitation - Ferreira, Bruno (2020)
Conventional motor rehabilitation therapies followed bystroke survivors during their recovery process are typically intense and involve numer-ous repetitions of task-specific recommended exercises. However, due to the lack of short-term or immediate results, patients tend to lose motivationonthe reha-bilitationprocess,and on performing the therapist recommended exercises at home between sessions. The work described in this article proposesto engage the patients withthetherapeutic exercisesby transforming the latter into speciallydesigned serious games. After an initial evaluation by therapists, a pilot study was conducted on a rehabilitation clinic that showedthat this system isadequatefor about 75% of the clinical cases treated. The proposedgame was globally well-accepted by patients, showing to be motivational and engaging. These promising results lead us to believe that immersive-based gamescan indeed be a valuable aid for motor rehabilitation therapies